Cultural beliefs and behaviors of clients with coronary artery disease: A necessity in patient education - Ashghaly Farahani, M; Mohammadi, I; Ahmadi, F; Maleki, M (Advances in Nursing & Midwifery, 2008)
Background Cardiovascular diseases are one of the leading causes of death in Iran. Patient education program is one of the most important programs in prevention and treatment of these disorders and it is directly related to culture of those working with patients. Since cultural factors influencing on patient education for coronary artery diseases have not yet been studied in Iran, identifying them can be very effective in improving the quality of the related programs. Purpose This qualitative program was conducted to explore the effects of cultural beliefs and behaviors of patients with coronary artery diseases on their education. Methods 35 subjects including 18 nurses as main informants, 4 medical doctors, 9 patients and 4 family members of them as ancillary informants were selected by purposive sampling method and interviewed at two teaching hospitals in Tehran between 2005 and 2006. The interviews were continued until data saturation stage and analyzed in content. Results The subjects expressed a variety of influential factors on education in coronary artery diseases. Five themes were derived from data analysis: 1. cultural beliefs and patients’ habits of life style; 2. patients’ and health team’s beliefs regarding the condition and management; 3. hiding the diagnosis; 4. beliefs of patients, their families, nurses and physicians regarding educator; and 5. inability of educator in communicating with different ethnic groups. Conclusion Findings showed that cultural beliefs can precipitate and aggravate the disease. Identifying and explaining these beliefs are essential for effective patient education. Keywords: Cultural beliefs, Patient education, Coronary artery diseases, Qualitative approach.